Edukasi Alarm Minum Obat (Amino) untuk Meningkatkan Kepatuhan Minum Obat Hipertensi pada Penderita Hipertensi - Putri, Miko Eka; Sari, Mila Triana; Fithriyani, Fithriyani; Yanti, Rahmi Dwi (Universitas Baiturrahim, 2025)
The incidence of hypertension has always increased from 13.50 percent in 2018 to 23.63 percent in 2020. Based on the report of cases of non-communicable diseases in Jambi City in 2021 regarding hypertension seen from 20 Health Centers, Putri Ayu Health Center reached 3,178 people with 1,184 male patients, lower than women with 1,994 patients. The high rate of hypertension in Legok Village is not compliant in taking hypertension medication. For this reason, it is necessary to carry out community service for the Legok Village community regarding Education on Medication Alarms (Amino) to Increase Compliance in Taking Hypertension Medication in Hypertension Patients. This service aims to provide education to the community on how to increase compliance in taking hypertension medication in hypertension patients. Community service was carried out on May 22, 2023 in Legok Village, Jambi City. The method in implementing this activity is providing education on how to improve compliance of hypertension sufferers in taking hypertension medication, Media for providing education on Medication Alarm using leaflets and ppt.. The method to improve the ability of hypertension sufferers in compliance with taking medication is with one of the SATUSEHAT Mobile Applications. The results show that there is an increase in knowledge and compliance in taking hypertension medication. It is hoped that hypertension sufferers can utilize the alarm in maintaining compliance with taking medication